2011
DOI: 10.1029/2010wr009792
|View full text |Cite
|
Sign up to set email alerts
|

Global monthly water stress: 2. Water demand and severity of water stress

Abstract: [1] This paper assesses global water stress at a finer temporal scale compared to conventional assessments. To calculate time series of global water stress at a monthly time scale, global water availability, as obtained from simulations of monthly river discharge from the companion paper, is confronted with global monthly water demand. Water demand is defined here as the volume of water required by users to satisfy their needs. Water demand is calculated for the benchmark year of 2000 and contrasted against bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
403
1
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 414 publications
(442 citation statements)
references
References 56 publications
7
403
1
3
Order By: Relevance
“…Unlike the work of Wada et al (2011) who used a crop growth model to estimate monthly irrigation water requirements, crop water requirements in GCAM are computed using a simplified methodology that utilizes estimated coefficients of water requirement per crop type and AEZ from crop growth models to efficiently compute irrigation water on an annual basis (see Chaturvedi et al, 2013). This reduced form is essential to the computational feasibility of iterating food demands and prices hundreds of iterations in each GCAM time period without resorting to running a crop growth model that many times.…”
Section: Irrigationcontrasting
confidence: 44%
See 4 more Smart Citations
“…Unlike the work of Wada et al (2011) who used a crop growth model to estimate monthly irrigation water requirements, crop water requirements in GCAM are computed using a simplified methodology that utilizes estimated coefficients of water requirement per crop type and AEZ from crop growth models to efficiently compute irrigation water on an annual basis (see Chaturvedi et al, 2013). This reduced form is essential to the computational feasibility of iterating food demands and prices hundreds of iterations in each GCAM time period without resorting to running a crop growth model that many times.…”
Section: Irrigationcontrasting
confidence: 44%
“…Wada et al (2011) suggested an R of 0.1 based on their assessments in Spain and Japan. However, this term is found to be closer to around 1.0 in the US, based on four cities that lie within four climate zones (See Fig.…”
Section: Domesticmentioning
confidence: 99%
See 3 more Smart Citations